PENGARUH PACK CARBURIZING ARANG ENCENG GONDOK TERHADAP LAJU KOROSI CAST IRON ALAT TURBOCHARGER - Nurmala Santi Dera; Indrawan Laria Indrawan; Novriyanti Talango Novriyanti; Sahional Ishak Sahional (JURNAL ILMIAH MOMENTUM, 2025)
Corrosion resistance is a crucial factor in extending the service life of cast iron turbocharger components, particularly in corrosive environments. One effective approach to enhance corrosion resistance is through the pack carburizing process, which forms a protective carbon layer on the material’s surface. In this study, water hyacinth charcoal was utilized as an alternative carbon source due to its environmentally friendly and economical characteristics. The research aimed to evaluate the effect of varying pack carburizing durations on the corrosion resistance of cast iron turbochargers and to characterize the macrostructural changes on the surface resulting from the treatment. The methodology involved a pack carburizing process with holding times of 2, 4, and 6 hours at a controlled temperature, followed by electrochemical corrosion testing. Macrostructural characterization was also conducted to observe surface morphology changes due to carbon diffusion. The test results showed that the untreated specimen had a corrosion rate of 0.180 mm/y, which decreased to 0.120 mm/y after 2 hours of carburizing. A more significant reduction was observed in the 4-hour specimen, with a corrosion rate of 0.095 mm/y, representing a 47% decrease compared to the untreated sample. However, after 6 hours, the corrosion rate only slightly decreased to 0.090 mm/y, indicating that the carbon layer had reached saturation. Macrostructural observations confirmed the formation of a more homogeneous carbon layer in the 4-hour specimen, while the 6-hour specimen exhibited a thicker layer with diminishing protective effectiveness. This study demonstrates that pack carburizing using water hyacinth charcoal can significantly enhance the corrosion resistance of cast iron turbochargers, with an optimal treatment duration of 4 hours for maximum protection. Keywords: pack carburizing, water hyacinth charcoal, cast iron, corrosion resistance, mechanical properties